The Representation of Themes and Moral Values in Banjar Fairy Tales - Jumadi Jumadi; Faradina Faradina; Ahsani Taqwiem; Lita Luthfiyanti (Universitas Lambung Mangkurat, 2025)
This study examines the thematic structure and moral values in Banjar fables and their relationship with socio-cultural aspects and the natural landscape of Banjar society. Banjar fables not only serve as a means of entertainment but also as a tool for moral education that encourages critical thinking about social conditions. These fables implicitly teach values such as courage, honesty, and social responsibility through their stories and characters. This study also highlights the importance of utilizing Banjar fables in school learning to preserve cultural heritage and prevent the erosion of national culture by foreign influences. Additionally, the findings open opportunities for further research on other genres of old Banjar literature, such as myths, legends, and sagas. This study employs a qualitative approach with thematic analysis of available Banjar fables, though data limitations are a significant consideration. These findings are expected to serve as a learning resource and reference for the development of character education and cultural literacy in Indonesia.